Enhanced performance of PV systems using a smart discrete solar tracker with fuzzy-ant colony controller - Abadi, Imam; Elchoir, Najela Rafia; Musyafa, Ali; Hadi, Harsono; Fitriyanah, Dwi Nur (Institute of Advanced Engineering and Science, 2025)
A solar tracker is a combination of mechanical and electrical systems that can be used to move a solar panel to follow the sun's direction. This solar tracker system is expected to optimize the output power of photovoltaics. Based on existing research, many solar tracking systems have been developed using active tracking methods to increase the power consumption of the components of solar trackers. Therefore, a passive solar tracking system was used to reduce the solar tracker's internal energy consumption. In this study, a passive smart discrete solar tracker was designed with 3 positions and 5 tracking positions based on a fuzzy-ant colony controller (ACO). The design of a passive solar tracker based on a fuzzy-ACO has a performance index (average) with a rise time of 0.45 s, a settling time of 0.701 s, a maximum overshoot of 0.5%, and a steady-state error of 0.05%. From the design, the 3-position passive solar tracker with fuzzy-ACO control can increase efficiency with a gross energy gain of 42.79% for 10 hours compared to a fixed PV. The 5-position passive solar tracker using fuzzy-ACO control increased the efficiency with a gross energy gain of 43.99%.